Sick Building Syndrome in Nurses of Intensive Care Units and Its Associated Factors - Sare Jafakesh; Leila Mirhadian; Zahra Atrkar Roshan; Mohammad Javad Gol Hosseini (Journal of Holistic Nursing and Midwifery)
Introduction: Sick Building Syndrome (SBS) is a set of undesirable physical and psychological conditions whose symptoms appear when entering the building and disappear after leaving it. The most well-known symptoms of SBS include problems of nervous and respiratory systems and skin. Since nurses spend many hours in the hospital and enclosed spaces, they are exposed to many factors related to the SBS, which can affect their health and the quality of patient care. Objective: This study aimed to investigate SBS and its related factors in nurses working in special care units of hospitals. Materials and Methods: This is a cross-sectional study in 2016 on 144 working nurses of special care units at educational and treatment centers in Rasht City, Iran. They were randomly selected proportional to the number of nurses working in each special care unit. For evaluating SBS symptoms and indoor air quality, the “Miljömedicin 040 Questionnaire” (English version A) was used. The collected data from the questionnaire were analyzed using the Chi-squared and Independent t-tests. Results: About 47.2% of nurses complained of SBS. The most common symptoms of this syndrome were headache, fatigue, heavy-headed feeling, concentration difficulty, and nausea/dizziness. According to the Chi-squared test results, there was a significant correlation between SBS and variables of air movement, fluctuating room temperature, stuffy bad air, dry air, too much light, light reflection, dust and dirt in the workplace, and contact with static electricity (P<0.05). Conclusion: There is a high prevalence of SBS among (nearly half of) the study nurses and it has a relationship with factors such as air movement, fluctuating room temperature, stuffy bad air, dry air, too much light, light reflection, dust and dirt in the workplace, and contact with static electricity. It is recommended that workplace cleanliness, the ventilation system quality, and standard lighting level in special care units be improved. Also, it is very important the nurses working in special care units know the factors associated with SBS.